Inhabited historical city ”Contemporary living/Historic hoce". Manifest from Arequipa to Latin American - Loayza Vela, Mónica (2020)
What if beyond rehabilitate housing of our historical center, to generate passing uses, contemplative and beautiful, we propose among all manage your integral renewal? Can we amplify our collective identity and retrieve the relationships that give us rights as ‘patrimonial subjects’? Proposals are admitted.Our City was not like this from the beginning, as you can imagine. At the time it was a boy village. There was another city below this, and another and another more of ashlars yellow sun and unpaved streets. And by one of those little streets, our parents and grandparents grew up, much of present body they lived. And that was the moment and the light of them.But now for us is different, we maintain a disclosed a memory of the past which generally deconstructs our historic city, reconfiguring scenarios and people, in the absence of housing, denying them a true connection with the time and diversity in its historical union. And that is precisely the reason and the search of our manifest.